2014
DOI: 10.1007/s11604-014-0375-0
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective statistical analysis of the late complications associated with central venous port placements

Abstract: Steroid administration and TPN were associated with increased rates of infection. In addition, patients receiving chemotherapy or whose CV ports are left in place for a long time should be carefully observed to decrease these complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
(11 reference statements)
2
9
0
Order By: Relevance
“…In a retrospective single-center analysis of 264 implanted port catheters, 50 (18.9%) had to be removed due to infection, suspected infection or catheter problems [29]. In an Italian study, a catheter-related complication rate of 7% was reported [30].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective single-center analysis of 264 implanted port catheters, 50 (18.9%) had to be removed due to infection, suspected infection or catheter problems [29]. In an Italian study, a catheter-related complication rate of 7% was reported [30].…”
Section: Discussionmentioning
confidence: 99%
“…3134 Despite this variability, which could be ascribed to various factors related, for example, to the type of population studied or to the study design, there is no doubt that TIVAD-related infection is the most frequent indication to port removal. 26,27,29,3538 In a recent French study on a cohort of patients with solid tumors, port-related infections required TIVAD removal in 81% of the cases, while conservative treatment was feasible only in a minority of patients. 37 Moreover, in the same study, 48% of the TIVAD-related infections were associated with complications, including 25% of septic shock.…”
Section: Epidemiologymentioning
confidence: 99%
“…Numerous studies investigating complications associated with ports and the associated risk factors have been performed, with reported overall complication rates ranging from 7.2% to 32.1%. [2][3][4] Such complications are often divided into procedural, early complications (<30 days) and late complications (⩾30 days). 5 complications include catheter malposition or migration, arterial rupture, pneumothorax, wound dehiscence, and infection, with complication rates of 0.7% to 4.6%.…”
Section: Introductionmentioning
confidence: 99%
“…6 Late complications, including infection, venous thromboembolism (VTE), extravasation, and mechanical failure, have higher reported incidence rates of 1.9% to 17.0%. 3,6,7 Of these, infection and VTE have the highest reported incidence rates, ranging from 2.3% to 22.0% and 0.1% to 18.0%, respectively. 7 The rate of complications necessitating device removal is reported to be 6% to 7%.…”
Section: Introductionmentioning
confidence: 99%